(untitled) (Eureka Journal of Humanities and Social Research, 2026)
The publisher plays a crucial role in the book publishing process, acting as the intermediary between the author and the market. This article explores the multifaceted responsibilities of publishers, including manuscript evaluation, editing, design, production, marketing, and distribution. By managing these tasks, publishers ensure the quality and commercial success of a book, while also protecting the rights of authors and meeting readers’ expectations. The publisher’s role is essential in transforming a manuscript into a finished product that reaches and resonates with its audience.